Critical performativity and the small firm: Challenges and prospects. (June 2018) - Edwards, Paul
The idea of engaging directly with management practice while retaining a strongly critical social science stance has become popular under the banner of critical performativity. This idea has yet to be applied to small firms, and it also needs specification: as usually stated, it lacks grounds within science to define with whom to engage and with what goals. In total, three themes are addressed: the nature of a 'radical pluralist' view of engagement, the distinct challenges in a small firm context and a set of three illustrations of possible lines of engagement. Engagement is both desirable and feasible, though large challenges remain, notably the demands of small-firm owners and the requirements of close engagement over a period of time.